2019
DOI: 10.1177/0192623319880445
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity Assessment of Daprodustat (GSK1278863), a Hypoxia-Inducible Factor (HIF)-Prolyl Hydroxylase Inhibitor

Abstract: Daprodustat (GSK1278863) is a hypoxia-inducible factor (HIF)-prolyl hydroxylase (PHD) inhibitor in development for treatment of anemia of chronic kidney disease. Daprodustat’s biological activity simulates components of the natural response to hypoxia; inhibition of PHDs results in HIF stabilization and modulation of HIF-controlled gene products, including erythropoietin. The carcinogenic potential of daprodustat was evaluated in 2-year carcinogenicity studies in Sprague-Dawley rats and CD-1 mice, where once-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…153 To date, animal studies have shown no evidence that prolonged exposure to HIF-PHIs is prooncogenic. 140,154,155 Although preliminary data from phase 3 roxadustat studies indicated that the rates of neoplasm-related AEs were not increased compared with placebo or epoetin alfa in patients with NDD CKD or DD CKD, 156 long-term observations in humans are needed to rule out any possible prooncogenic properties of HIF-PHIs. Given the multiple theoretical safety concerns and the exclusion of patients with a history of cancer (<2-5 years) from clinical trials, the use of HIF-PHIs in patients with cancer should not be recommended, as safety data are not available.…”
Section: Renal Safetymentioning
confidence: 99%
“…153 To date, animal studies have shown no evidence that prolonged exposure to HIF-PHIs is prooncogenic. 140,154,155 Although preliminary data from phase 3 roxadustat studies indicated that the rates of neoplasm-related AEs were not increased compared with placebo or epoetin alfa in patients with NDD CKD or DD CKD, 156 long-term observations in humans are needed to rule out any possible prooncogenic properties of HIF-PHIs. Given the multiple theoretical safety concerns and the exclusion of patients with a history of cancer (<2-5 years) from clinical trials, the use of HIF-PHIs in patients with cancer should not be recommended, as safety data are not available.…”
Section: Renal Safetymentioning
confidence: 99%
“…At least two agents have been assessed regarding their potential for cancer development in longer‐term murine studies: roxadustat and daprodustat 34,35 . Roxadustat is usually administered to humans at doses up to 1.5 mg/kg daily or thrice‐weekly (TIW).…”
Section: Potential Concerns Of Hif‐phimentioning
confidence: 99%
“…At least two agents have been assessed regarding their potential for cancer development in longer-term murine studies: roxadustat and daprodustat. 34,35 Roxadustat is usually administered to humans at doses up to 1.5 mg/kg daily or thrice-weekly (TIW). At doses of up to 10 (rats) and 60 (mice) mg/kg administered TIW and followed for up to 104 weeks, there was no effect in either animal on survival or on the development of neoplastic lesions.…”
Section: Supplementation Of Iron and Monitoring Of Iron Statusmentioning
confidence: 99%
“…and Mol [148]. Daprodustat PHD1>PHD3>PHD2 -High doses of drugs did not show carcinogenic potential in vivo [150].…”
Section: Roxadustatmentioning
confidence: 96%
“…Daprodustat [156], developed by GlaxoSmithKline, preferentially inhibits PHD1 and PHD3 [145] and both HIF1α and HIF2α isoforms stabilize upon treatment, attesting to its efficacy in activating the hypoxia pathway. Importantly, no carcinogenicity potential was detected for this compound even at high pharmacological doses [150]. Daprodustat was also effective in a mouse LLC model as it resulted in better normalization of the tumor vessels with enhanced pericyte coverage that was linked to diminished presence of angiogenic factors.…”
Section: Roxadustatmentioning
confidence: 99%